Hypolipidemic effect of Silymarin in Dyslipidaemia of Different Etiologies - Mesheimish, Bahir Abdul Razzaq; Hussain, Saad Abdul-Rehman; Ismail, Sajida Hussein; Hussein, Khalid Brahmani; Sulaiman, Amaal Ajaweed (Journal of the Faculty of Medicine Baghdad, 2008)
Background: Many drug and non drug approaches are utilized for the treatment of dyslipidemia; flavonoids, the major constituents of silymarin, have been proved topositively modify lipoproteins in experimentally – induced dyslipidemia. Objective: This study was designed to evaluate the effect of silymarin, when used alone or in combination with other hypolipidemic agents, on the lipid profile indyslipidemic patients. Patients and Methods: Fifty seven patients with dyslipidaemia of various etiologies are involved in this clinical trial. They are randomized into three groups treated witheither 400mg / day silymarin (gr. A) or 20 mg / day lovastatin (gr. B) or a combination of 200 mg/day silymarin and 10 mg/day lovastatin (gr. C) for 2 months, only 45patients complete the study . Serum lipid profile (total cholesterol, triglycerides, LDLC, VLDL-C and HDL-C) and liver functions indices (SGOT, SGPT, total bilirubin)were evaluated each month during the follow up period.Results: Treatment with silymarin results in a significant decrease in TC, TG, LDL-C and VLDL-C levels, with a significant elevation in HDL-C levels, without anysignificant changes in liver function. Meanwhile, adjunct use of silymarin with lovastatin widens the scope of lovastatin-hypolipidemic effect, without increasing inthe score of adverse effects, and ameliorating the hepatic damage emerged due to its use.Conclusions: The results presented in this study indicated that silymarin can be used alone in clinical practice for the treatment of dyslipidemia, and when combined withother hypolipidemic agents like lovastatin, improves therapeutic profile and ameliorate some of its adverse effects.